Self Deprecating Humor dalam Komunikasi Politik - Salma Azizah Nurwirastari; Mahfud Anshori (Jurnal Komunikasi Massa, 2025)
Self-deprecating humor is a form of humor in which an individual consciously belittles or mocks themselves. In political communication, this strategy is used to build rapport with the audience, mitigate criticism, and shape the authentic image of a politician. This study examines the use of self-deprecating humor in political communication through the lens of the Elaboration Likelihood Model (ELM), which differentiates message processing routes into central and peripheral routes. The literature review indicates that this type of humor can enhance a politician’s credibility, particularly among audiences with low issue involvement, but also has limitations when engaging audiences who critically assess political message content. This study also highlights how social media has become a primary medium for politicians to disseminate political humor, particularly on platforms such as TikTok and Twitter. However, research gaps remain regarding the effectiveness of self-deprecating humor across different cultures and its impact on public political participation. Therefore, future research is recommended to further explore the relationship between issue involvement and humor processing, as well as to analyze the influence of political humor on politician credibility through experimental studies.